A Framework for Intra-Organizational Cluster Knowledge Management Based on Ontology - Abubakar Rufai Garba; Umar Danjuma Maiwada; Halima Bamali Nourah (East Asian Journal of Multidisciplinary Research, 2022)
The ability of an organization to share knowledge is viewed as a competitive advantage platform. A corporation must have processes in place to encourage and facilitate knowledge exchange inside the organization in order to acquire this advantage. The key elements that influence employees' knowledge comprehension are organizational and individual characteristics. A knowledge-based system called ontologies is required for personnel to properly cooperate and exchange knowledge. Ontology will provide innovative problem solving for searching and sharing their knowledge and experience by creating a cluster within the organization through the implementation of a search mechanism for effective communication This paper is aimed at investigating the emerging technology of Semantic Web and Ontology to design Ontology-Based Knowledge Management System (OKMS) for intra-organization that will support knowledge management activities. This was accomplished by establishing a cluster inside the organizational structure that will allow for unfettered information flow throughout the group of firms, boosting effective communication among the company's employees and optimizing profit. The modified waterfall model was used to create the system. The result demonstrates how learning, unlearning, relearning, and reflection are used to get the right knowledge to the right people at the right time, as well as assisting people in sharing and utilizing the information, developing and reflecting previous experiences, and practices for sharing knowledge to improve organizational performance and develop core-competencies. As a result, it's critical to comprehend the types of information exchanged and how an organization's expectations impact knowledge sharing among its members.